Analysis of factors nurse turnover: A qualitative research - Efrata, Efrata (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
The resignation of nurses is a loss for hospitals because they have to recruit new nurses accompanied by orientation towards them. Of course, the newly recruited nurses cannot provide optimal performance because they still need an adjustment period. Many factors cause nurse resignations, both internal and external to the hospital.  carry out a qualitative analysis of the factors that cause a nurse to decide to resign so that preventive measures can be taken. The research was conducted qualitatively by interviewing 15 informant who decided to resign from RSU Sembiring during the period November and December 2023. The interview results were analyzed using a thematic analysis model to produce themes which were factors causing nurse resignation. There are five themes found in the research which are the causes of nurses' resignation, namely: taking care of children, following their husband, continuing their education, getting another job and incompatibility with co-workers. There are 2 causes of nurse resignation, namely internal and external factors of the nurse. Internal factors are caused by the obligations that nurses must carry out in the form of: looking after children and accompanying their husbands, and the opportunity to continue education. Meanwhile, external factors are related to the hospital institution, namely incompatibility with colleagues and the environment in the form of job offers from other hospitals. Efforts to improve the welfare of nurses in the form of: increasing salaries, providing child care, opportunities to continue their education and holding family gatherings need to be carried out by hospital management.